Analisa Perancangan Sistem Informasi E-Commerce Dengan Metode Object Oriented dan ISO 9126 pada PT.Samudera Semesta Sejahtera - Tanto Heryanto; Yakub Yakub (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
PT. Samudera semesta sejahtera is a freight forwarding company that handle export and import. The main problem is the document of export such as : there still promoting their service via telephone by the office and by the email. Also sometimes they miss the documents that sometimes will be need back. Manual booking, e-commerce using unified modelling language (UML); activity diagram, usecase diagram, sequence diagram, and class diagram. Using object oriented and iso 9126, the programming language that use in this e-commerce system is PHP and database MySQL. The result of this e-commerce is for business, making easier to search data or information, and printing a report.